2020
DOI: 10.1109/lsens.2020.3018820
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Aid Among Sensors: An Emergency Function for Sensor Networks

Abstract: A large number of wireless sensor nodes in a certain area results in high contention. Inevitably, the transmissions of any possible critical data packets may fail due to collisions. In this article, we introduce an aspect of human intelligence in wireless sensor networks, influenced by cooperative networking, which enhances the timely delivery of critical data. Mutual aid among sensors (MAAS), is an emergency out-of-the-box medium access control (MAC) function for IEEE 802.15.4-2020. Specifically, the network … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In [201], the authors suggest an algorithm for retrieving and storing information on WSNs in post-disaster scenarios to help the rescue team. To improve the delivery of mission critical data, human intelligence is embedded in a wireless sensor network where the network coordinator can detect the critical data and sets an emergency flag at its next beacon to inform the nodes [202].…”
Section: G Wireless Sensor Network (Wsn)mentioning
confidence: 99%
“…In [201], the authors suggest an algorithm for retrieving and storing information on WSNs in post-disaster scenarios to help the rescue team. To improve the delivery of mission critical data, human intelligence is embedded in a wireless sensor network where the network coordinator can detect the critical data and sets an emergency flag at its next beacon to inform the nodes [202].…”
Section: G Wireless Sensor Network (Wsn)mentioning
confidence: 99%
“…In recent years, the use of Inductive Power Transfer (IPT) has increased in many applications where cables are not desired or cannot be used, such as medical implants [1], wireless sensor nodes [2], smart textile wearable devices [3], electrical vehicles [4], and robots [5]. Typically, IPT systems are based on coupled-mode theory in an oscillating electromagnetic field with a transmitter coil (TX) and a receiver coil (RX), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Ordinary smart grid users can view and manage other electric devices at home through the meter, and equipment maintainers upgrade and maintain the grid devices by upgrading them. Depending on the functions of the grid customers in the smart grid, the grid users have different access rights to the smart devices, and in this smart grid system with multiple devices can access these grid devices accordingly according to the needs of the grid customers in different roles and modification operations according to the needs of different roles of grid customers [6][7][8][9][10]. Quantum computing will potentially enable the computational power of ordinary computers to greatly exceed the present computational power, and in 1997, Shor et al proposed quantum algorithms for solving the decomposition of large integers and discrete logarithms and demonstrated that the time complexity of their algorithmic operations is of polynomial level [11].…”
Section: Introductionmentioning
confidence: 99%